Multiobjective Optimization as Alternative Search of Sustainable Composite Structures - Carlos Alberto Conceição António (2015)
More attention is being paid these days to sustainable design. The recent increases in structural material prices is further evidence that global consumption will raise both awareness and need to design for the efficient and rational use of materials. From a structural engineering point of view the biggest impact can be made by focusing on optimizing the structural systems to reduce the material requirements of a project supported by sustainability concepts. The integration of the materials selection process into optimization must be seen as tool to reach the sustainability of composite structures being the scope of the proposed multiobjective design approach.